Exploring Humanism in Buddhism: An In-Depth Study of Humanist Values at the Indonesian Tzu Chi Buddhist Foundation - Madiyono, Madiyono; Syukur, Abdul (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
This research is based on the initial concept of Buddhist teachings, which emphasize overcoming suffering. However, as time went on, some Buddhist practices were deemed not to have fully reduced suffering and social problems, giving rise to the Humanistic Buddhism movement. The purpose of this study is to examine the humanistic values ​​in Buddhist teachings practiced by the Indonesian Tzu Chi Buddhist Foundation and to examine the strategies employed to develop and preserve these values. This research employed qualitative methods with sociological and phenomenological approaches. Data were collected from primary and secondary sources, including the Tipiṭaka/Tripṭaka, Sūtra Mahāyāna, books, magazines, online media, as well as observation, documentation, and interviews. Interviews were conducted with leaders, volunteers, and beneficiaries of the Tzu Chi Foundation in West Jakarta using the snowball technique. Data were analyzed using the Miles-Huberman and Saldana techniques, while their validity was tested by triangulation and extended research time. The results of the study indicate that the humanist values ​​contained in the teachings of Buddha and Master Cheng Yen include equality, love, compassion, altruism, tolerance, brotherhood, wisdom, concern for nature, generosity, morality, patience, sincerity, gratitude and open-mindedness. These values ​​are implemented in four missions and eight Dharma footprints, namely charitable missions, health, education, humanist culture, international disaster relief, bone marrow donation, environmental conservation, and community volunteer involvement. This study concludes that the development and preservation of humanist values ​​in Tzu Chi is carried out through resource mobilization, utilization of political opportunities, and framing processes, so that Tzu Chi can be understood as a unique Buddhist social religious movement that is also reformist in nature.